Strategi Pengembangan Sumber Daya Manusia (SDM) pada UMKM Kota Palu di Era Pandemi Covid 19 - Risnawati Risnawati; Wiri Wirastuti; Sriwanti Sriwanti; Fera Fera; Surayya Surayya; Asriadi Asriadi; Meggi Indrianinangsih (Jurnal Ilmiah Aset, 2022)
The background in this study is that the role of MSMEs is very strategic, especially in overcoming poverty and employment so that they can empower the community well. During the COVID-19 pandemic, culinary SMEs typical of the city of Palu experienced an impact on their business processes, and experienced a significant decline in sales. This research uses descriptive qualitative method. Data were collected through questionnaires, and interviews. Respondents in this study amounted to 25 owners of culinary SMEs typical of the city of Palu. The results of this study obtained a strategy for developing human resources for culinary SMEs typical of the city of Palu: HR training on digital marketing, product innovation, financial transaction applications, and creativity programs organized by the government and other business groups.